SVD-Based Precoding for Single Carrier MIMO Transmission With Frequency Domain MMSE Turbo Equalization - Grossmann, M. (IEEE signal processing letters, 2009)
This letter proposes an SVD-based precoding technique for single carrier transmission over frequency selective MIMO channels with frequency domain (FD) minimum-mean-squared-error (MMSE) turbo equalization. We consider the problem of optimizing the transmit power allocation over the FD channel eigenmodes subject to maintaining a target bit error rate of the turbo equalizer, and show that this problem can be efficiently solved by convex programming techniques. Results of the simulations conducted to demonstrate the superiority of the turbo equalizer with the proposed precoding technique, and to verify the accuracy of the analysis are presented in this letter.